Development of protein degradation inducers of oncogenic BCR‐ABL protein by conjugation of ABL kinase inhibitors and IAP ligands - Shibata, Norihito (Cancer Sci, 2017)
Chromosomal translocation occurs in some cancer cells, which results in the expression of aberrant oncogenic fusion proteins that include BCR‐ABL in chronic myelogenous leukemia (CML). Inhibitors of ABL tyrosine kinase, such as imatinib and dasatinib, exhibit remarkable therapeutic effects, although emergence of drug resistance hampers the therapy during long‐term treatment. An alternative approach to treat CML is to downregulate the BCR‐ABL protein. We have devised a protein knockdown system by hybrid molecules named Specific and Non‐genetic inhibitor of apoptosis protein [IAP]‐dependent Protein Erasers (SNIPER), which is designed to induce IAP‐mediated ubiquitylation and proteasomal degradation of target proteins, and a couple of SNIPER(ABL) against BCR‐ABL protein have been developed recently. In this study, we tested various combinations of ABL inhibitors and IAP ligands, and the linker was optimized for protein knockdown activity of SNIPER(ABL). The resulting SNIPER(ABL)‐39, in which dasatinib is conjugated to an IAP ligand LCL161 derivative by polyethylene glycol (PEG) × 3 linker, shows a potent activity to degrade the BCR‐ABL protein. Mechanistic analysis suggested that both cellular inhibitor of apoptosis protein 1 (cIAP1) and X‐linked inhibitor of apoptosis protein (XIAP) play a role in the degradation of BCR‐ABL protein. Consistent with the degradation of BCR‐ABL protein, the SNIPER(ABL)‐39 inhibited the phosphorylation of signal transducer and activator of transcription 5 (STAT5) and Crk like proto‐oncogene (CrkL), and suppressed the growth of BCR‐ABL‐positive CML cells. These results suggest that SNIPER(ABL)‐39 could be a candidate for a degradation‐based novel anti‐cancer drug against BCR‐ABL‐positive CML.